Prevalence and attitude towards cigarette smoking among young adults in rural and urban communities in Kano State, North-Western Nigeria - Ibrahim Shehu, Aliyu; Mohammed, Nazeef; Zakka, Musa; Iliyasu, Usman; Ibrahim, Aisha Aliyu; Abulfathi, Aisha Aliyu; Kwaku, Amina (International Journal Of Community Medicine And Public Health, 2025)
Background: Cigarette smoking is a primary cause of preventable death worldwide, killing more than 7 million people annually. It poses a major public health challenge, as over half of 1.2 billion smokers are young adults. The prevalence and attitudes toward cigarette smoking among young adults in Kano State’s rural and urban areas are poorly understood. This study aimed to assess and compare the prevalence and attitudes toward cigarette smoking among young adults in these communities. Methods: A comparative cross-sectional descriptive study design was employed. Structured, interviewer-administered questionnaires adapted from the modified WHO global youth tobacco survey were administered to 894 young adults (urban; 447 and rural; 477) selected using a multistage sampling method. Data were analysed using IBM SPSS statistics v20. Results: The overall prevalence of ever smoking among young adults was 24.8% (95% CI: 22.1-28.1), significantly higher in rural (30.3%, 95% CI: 26.0-35.0) than urban communities (19.4%, 95% CI: 15.8-23.3) (p<0.001). The overall prevalence of current smoking was 14.5% (95% CI: 12.2-17.0), higher in rural (16.7%, 95% CI: 13.3-20.4) than urban communities (12.2%, 95% CI: 9.1-15.3), although not statistically significant (p=0.065). Over half of the respondents had a positive attitude toward cigarette smoking, with a higher proportion in urban compared to rural communities (p<0.05). Conclusions: The prevalence of cigarette smoking was higher in rural than urban communities. Urban communities showed positive attitudes toward smoking. Maintaining positive attitude towards smoking affects quitting.